Terrestrial ecosystems in a changing world - Canadell, Josep G. (Global Change - The IGBP Series, 2007)
Over 100 authors present 25 contributions on the impacts of global change on terrestrial ecosystems including: key processes of the earth system such as the CO2 fertilization effect, shifts in disturbances and biome distribution, the saturation of the terrestrial carbon sink, and changes in functional biodiversity, ecosystem services such the production of wheat, pest control, and carbon storage in croplands, and sensitive regions in the world threaten by rapid changes in climate and land use such as high latitudes ecosystems, tropical forest in Southeast Asia, and ecosystems dominated by Monsoon climate. The book also explores new research developments on spatial thresholds and nonlinearities, the key role of urban development in global biogeochemical processes, and the integration of natural and social sciences to address complex problems of the human-environment system.